Impact of Parkinson’s Disease on Functional Mobility at Different Stages - Mollà-Casanova, Sara; Pedrero-Sánchez, Jose; Inglés, Marta; López-Pascual, Juan; Muñoz-Gómez, Elena; Aguilar-Rodríguez, Marta; Sempere-Rubio, Nuria; Serra-Añó, Pilar (Frontiers in Aging Neuroscience, 2022)
Introduction: Specific functional assessments to determine the progression of Parkinson’s Disease (PD) are important to slow down such progression and better plan rehabilitation. This study aimed to explore possible differences in the performance of different functional tasks included in a mobility test using sensors embedded in an Android device, in people at different PD stages. Methods: Eighty-seven participants with PD agreed to participate in this cross-sectional study. They were assessed once using an inertial sensor and variables related to functional status were recorded (i.e., MLDisp, APDisp, DispA, Vrange, MLrange, PTurnSit, PStand, TTime and RTime). Results: There was a significant impairment of the vertical range during gait between stages I and II. Further, when stages II and III were compared, the sit to stand power was significantly impaired and the total time required to complete the test increased significantly (p<0.05). Even more significant differences were obtained when stages I and III were compared, in particular, dysfunction in postural control, vertical range, sit to stand power, and total time. Finally, there were no significant differences between stages in the medial-lateral displacements and reaction time (p>0.05). Conclusion: Functional mobility becomes more significantly impaired in the PD population as the PD stages progress. This implies impaired postural control, decreased ability to sit down or stand up from a chair, increased metabolic cost during walking and overall slowing-down of motor function.